2x +6=x+2 3(x-1)+2x=x+5
Anexe:
Răspunsuri la întrebare
Răspuns de
1
2x + 6 = x + 2
2x - x = - 6 + 2
x = - 4
3(x - 1) + 2x = x + 5
3x - 3 + 2x = x + 5
5x - x = 3 + 5
4x = 8
x = 8/4
x = 2
2x - x = - 6 + 2
x = - 4
3(x - 1) + 2x = x + 5
3x - 3 + 2x = x + 5
5x - x = 3 + 5
4x = 8
x = 8/4
x = 2
Răspuns de
1
×=-4 mai mic ca = 2
.......
Alte întrebări interesante
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă